Comparative assessment of energy costs of stacker crane movements - Korytov M.S.; Bezrodina A.E. (Naučno-Tehničeskij Vestnik Brânskogo Gosudarstvennogo Universiteta, 2024)
Within the framework of the put forward hypothesis that energy costs of working movements of the links of racking stacker cranes are inextricably linked to the shape of the working area of the warehouse in which the crane operates, to reduce energy costs, it was pro-posed to use a rotating boom in the design of the stacker crane. With the help of program implementations of mathematical models of stacker cranes of traditional bicycle design and the proposed design with a rotating boom, it became possible to determine the average energy costs for all possible movements of loads of the same mass within the corresponding working areas of these designs. For this purpose, systems of differential equations in Cauchy form were developed, where dissipation of energy was taken into account. The total value of work of crane drives during acceleration and braking was determined. The latter were carried out with constant accelerations, and the movement after acceleration — with constant speeds. The developed simulation mathematical models of cranes of traditional design and the proposed design with a rotating boom allow to determine the energy costs in the drives when moving the crane links along the given trajectories. According to the criterion of average total energy costs, adopted for all possible combinations of movements within areas of the same capacity of one hundred square meters, the stacker crane of the proposed design has an advantage over the crane of traditional design. This makes it possible to significantly reduce energy costs when using such cranes in warehouses and hangars. It is reasonable to recommend the use of a stacker crane of the developed design in warehouses of round shape — it will allow to reduce significantly the energy costs when using such cranes in warehouses and hangars.